Causality Relationship between Trading Volume and Stock Return: Evidence from Nepalese Stock Market - Shrestha, Shivaram (PYC Nepal Journal of Management, 2016)
This paper aims to empirically examine the causal relation between trading volume and stock returns for Nepalese Stock Market using Garner causality procedure, using monthly data for the period of July 2007 to February 2015. The study analyzed for the investigation of the Granger causality between trading volume and stock price using monthly data sets to ascertain if the causality runs from volume to stock price or from stock price to volume or in both directions. This study detected unidirectional causality from stock returns to trading volume that is indicative of noise trading model of return volume interaction in this market.